Collection of sports medicine and sports science - bibliography 2006 (IOC Medical Commission, 2006)
This is the 2006 bibliography of the holdings of the IOC Medical Commission Collection of sports medicine and sports science at the IOC library for reference texts and scientific journals published until 2006.